Discrete Hours Labour Supply Modelling: Specification, Estimation and Simulation - John Creedy; Guyonne Kalb (New Zealand Government, The Treasury, 2003)
The assumption behind discrete hours labour supply modelling is that utility-maximising individuals choose from a relatively small number of hours levels, rather than being able to vary hours worked continuously. Such models are becoming widely used in view of their substantial advantages, compared with a continuous hours approach, when estimating and their role in tax policy microsimulation. This paper provides an introduction to the basic analytics of discrete hours labour supply modelling. Special attention is given to model specification, maximum likelihood estimation and microsimulation of tax reforms. The analysis is at each stage illustrated by the use of numerical examples.
Keywords: D10; C15; C25; C50; 330; Discrete hours labour supply; multinomial logit; maximum likelihood estimation; microsimulation